Characterisation of the immune microenvironment of cutaneous squamous cell carcinoma in immunosuppression. Issue 11 (26th July 2022) - Rajesh, Aarthi; Saito, Mayumi; Morrin, Helen; Tschirley, Allison; Simcock, Jeremy; Currie, Margaret; Hibma, Merilyn
Abstract: Cutaneous squamous cell carcinoma (cSCC) is a common cancer. Systemic immunosuppression with drugs such as Prednisone results in more aggressive disease. We hypothesise that more aggressive disease in immunosuppression is the result of immune changes in the tumor microenvironment. We characterised T cell, phagocytic and antigen presenting cell subsets in cSCC and determined if these infiltrates were altered by immunosuppressive therapy. We found a dominant "CD8 profile" in the centre of cSCC lesions, with CD8 cells correlating with Tbet, FoxP3, OX40 and "M2‐like" macrophages, whereas a "Tbet and granulocyte profile" with associated inflammation predominated at the margin of the tumor. Individuals on systemic immunosuppressive therapy had lesions that were comparable in size, stage and number of vessels to immune competent individuals; however, the number of CD11c positive cells in the lesion centre was significantly reduced. We conclude that cSCC lesions are immunologically heterogeneous across the lesion and that systemically immunosuppressed individuals have reduced CD11c positive cells in the centre of the lesion. The role and detailed phenotype of CD11c positive cells in cSCC lesions warrant further investigation.